Determination of Digital Density Efficiency by Data Envelopment Analysis: EU Member States - Esra G. Kaygısız (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
This study aims to determine the digital intensity levels, which are an indicator of the digital transformation performance of the countries. With this scope, the digital intensity efficiency levels of the European Union member countries were calculated by data envelopment analysis (DEA). The input-oriented Charnes Cooper and Rhodes (CCR-O) Model has been used to determine the digital intensity of the countries. The input criteria of the DEA model were obtained from the digital skills data in The Digital Economy and Society Index-2021 (DESI), and the output criteria were obtained from the digital intensity data of the same index. Digital content creation communication and collaboration, online information and communication, information and data literacy, problem-solving, and safety skills are input criteria for digital skills. Very low, low, high, and very high data were used as output criteria for digital intensity. According to the findings, Hungary, Spain, Slovakia, and Ireland are not at the full efficiency level. It is also stated in the study that input variables should be directed to reach the full efficiency level of the countries that are not at the full efficiency level. Accordingly, it was observed that Hungary, Spain, Ireland and Slovakia are not at the full productivity level. it can be said that these countries have digital skills but their digital intensity is not high. In this respect, it can be concluded that they do not make use of these skills sufficiently.